Three fourths a penny for your thoughts?: gender pay differentials in Trinidad and Tobago: an empirical analysis - Roopnarine, Karen Anne (2018)
The Caribbean is an understudied region in terms of gender wage gaps and this research adds new insights into the sparse economics literature on this topic for the region, and in particular, for the two-island state of Trinidad and Tobago. Economic inequality between men and women is a pertinent problem deserving of in-depth study because it has far-reaching inter-generational consequences. Furthermore, gender inequalities in the labour market are considered as indicators that considerably restrain economic growth. Trinidad and Tobago’s economy has undergone tremendous strides in terms of economic growth over the past 20 years, and this study provides a deeper understanding of how the gender pay gap evolved over that time period. The present analysis of the gender wage gap has allowed us to ascertain if working women in Trinidad and Tobago were able to benefit from the country’s improved economic prosperity.